2022
DOI: 10.3389/fneur.2022.855532
|View full text |Cite
|
Sign up to set email alerts
|

Association of Pre-stroke Frailty With Prognosis of Elderly Patients With Acute Cerebral Infarction: A Cohort Study

Abstract: BackgroundFrailty is a state of cumulative degradation of physiological functions that leads to adverse outcomes such as disability or mortality. Currently, there is still little understanding of the prognosis of pre-stroke frailty status with acute cerebral infarction in the elderly.ObjectiveWe investigated the association between pre-stroke frailty status, 28-day and 1-year survival outcomes, and functional recovery after acute cerebral infarction.MethodsClinical data were collected from 314 patients with ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Frailty is a condition characterized by the progressive deterioration of physiological functioning, which is closely related to adverse events such as falls, decreasing mobility, hindrances in the activities of daily life, hospitalization, and deaths [24]. Frailty leads to physical deterioration and reduced mobility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Frailty is a condition characterized by the progressive deterioration of physiological functioning, which is closely related to adverse events such as falls, decreasing mobility, hindrances in the activities of daily life, hospitalization, and deaths [24]. Frailty leads to physical deterioration and reduced mobility.…”
Section: Discussionmentioning
confidence: 99%
“…The FRAIL scale was published by Morley et al and used to assess frailty, which has been demonstrated as an excellent screening test for clinicians to identify frail persons at risk of developing disability as well as a decline in health functioning and mortality [14,24]. Although MRI is more accurate in assessing paraspinal muscle mass, it has the disadvantage of being timeconsuming, labor-intensive, and expensive.…”
Section: Discussionmentioning
confidence: 99%
“…Sarcopenia was estimated in 15.8% of patients with acute stroke (6). Notably, pre-stroke sarcopenia is independently associated with severe disability and high mortality rates (7,8). In addition, skeletal muscle has been considered an essential regulator of immune system function (9).…”
Section: Introductionmentioning
confidence: 99%
“…They suggested that future research should focus on which patients with stroke would benefit from specialty PC. 13 Current evidence suggests that a patient's prestroke frailty status impacts outcomes after acute stroke [14][15][16][17] and may be an appropriate trigger for PCC. However, the best way to screen for frailty after acute stroke has not been well explored.…”
mentioning
confidence: 99%
“…Current evidence suggests that a patient’s prestroke frailty status impacts outcomes after acute stroke 14-17 and may be an appropriate trigger for PCC. However, the best way to screen for frailty after acute stroke has not been well explored.…”
mentioning
confidence: 99%